Pogodbena odškodninska odgovornost strokovnjakov nasproti tretjim osebam - Dular, Drago (Podjetje in delo, 2022)
When an expert provides information in the exercise of his profession, this type of liability is including in the professional liability of members of individual occupational groups, e.g. lawyers, architects, auditors, tax consultants, and real estate appraisers. It is characteristic of these members that they work in the liberal professions, which is why they usually prepare expert opinions for their clients or subscribers based on appropriate contracts. Consequently, there is no doubt that an individual expert is liable to their client for damages if they produce a deficient expert opinion based on such a contract. However, the question is whether experts can also be liable to third parties who have relied on these opinions based on those contracts. In the former Jugoslav law, the courts did not recognise contractual liability towards third parties because they proceeded from the view that the contract creates legal effects only between the parties to the contract. If a third party was affected by an expert's opinion, it could claim compensation from a specific expert only on a tort basis. Such an opinion is also represented by Slovenian courts in the current period. In the article, the author proves that contractual liability of experts against third parties is also possible, referring to German and Austrian law. The author believes that Slovenian contract law provides all the conditions for enforcing the contractual liability of experts against third parties, and states the advantages of such a basis of responsibility, namely the occurrence of tripartite relations relating to third parties. A comprehensive treatment allowed by the contract based on proper interpretation is needed.
Keywords: contractual liability of experts against third parties; expert opinion contract; importance of expert opinion in legal transactions; importance of interpretation of contract; pogodba o izdelavi strokovnega mnenja; pogodbena odškodninska odgovornost strokovnjakov nasproti tretjim osebam; pogodbeno pravo; pomen interpretacije pogodb; pomen strokovnega mnenja v pravnem prometu; third party; tretja oseba; tripartite relations; tristranska razmerja